2021
DOI: 10.15294/lc.v16i1.31158
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of CTL Method in teaching English to the students of MAN 1 Enrekang

Abstract: This research shows the implementation of contextual teaching and learning conducted by the English teachers of MAN 1 Enrekang in teaching English. MAN 1 Enrekang is senior high school that is located in Enrekang regency, Sulawesi Selatan, as one of the schools where most of the teachers there implement CTL method in teaching, include teaching English. However, sometimes the students still find it difficult to understand the material being taught, especially English. This research employed descriptive qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
4
1
0
1
Order By: Relevance
“…They perceived the process of gathering and reading information through various sources in the inquiry element, as well as collaborating with their peers in the learning community element, to be valuable in improving their vocabulary knowledge. The findings of this study align with the conclusion drawn by Risan et al (2021), who observed that the implementation of CTL approach resulted positive results in terms of enhancing students' exposition writing skills, particularly in relation to the vocabulary component. The observed improvement in student performance can be attributed to the instructional strategy employed by the teacher.…”
Section: Findings and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They perceived the process of gathering and reading information through various sources in the inquiry element, as well as collaborating with their peers in the learning community element, to be valuable in improving their vocabulary knowledge. The findings of this study align with the conclusion drawn by Risan et al (2021), who observed that the implementation of CTL approach resulted positive results in terms of enhancing students' exposition writing skills, particularly in relation to the vocabulary component. The observed improvement in student performance can be attributed to the instructional strategy employed by the teacher.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Apart from the two supporting study above, the finding of this study is also aligned with some previous study (Hasani, 2016;Indrawati & Ayob, 2018;Risan et al, 2021). First, the students' skill in writing analytical exposition was improved through the development of their ability to construct their writing in accordance with the paragraph structure, which includes thesis statements, supporting arguments, and conclusion.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…The students' posttest result revealed that they performed their writing better after receiving the treatment. The finding was aligned with the previous studies (Hasani, 2016;Indrawati and Ayob, 2018;Wicaksono, 2019;Risan, et al 2021).…”
Section: Students' Analytical Exposition Writing Skillsupporting
confidence: 92%
“…Sebagai bahasa asing yang memiliki banyak fungsi, bahasa Inggris diajarkan sebagai mata pelajaran wajib sejak tahun pertama sekolah menengah pertama sampai tahun pertama di perguruan tinggi, bahkan saat ini diajarkan mulai dari sekolah dasar sebagai kurikulum muatan lokal (Risan et al, 2021)…”
Section: Pendahuluanunclassified